Variations among unbred heifers in the activities of polymorphonuclear leucocytes from the mammary gland and blood - Rysánek, D; Babák, V; Sládek, Z; Toman, M (Journal of veterinary medicine. B, Infectious diseases and veterinary public health, 2001)
The phenotypic characteristics are described for the activity of polymorphonuclear leucocytes NMN) obtained by either lavage of the cavity system of juvenile mammary glands stimulated with a synthetic muramyl dipeptide analogue or isolation from the peripheral blood. Attention was paid to the variability of characteristics and its sources, and to correlations among them. The following characteristics were investigated in 27 clinically healthy, unbred Bohemian Red Pied x Holstein heifers: migration activity in situ, number of phagocytosing PMN, phagocytotic index, bactericidal activity of PMN and unstimulated and zymosan-stimulated luminol-dependent chemiluminescence. Considerable individual variation was found in the characteristics. Significant differences between blood PMN and PMN from lavages after influx induction were found for bactericidal activity (P < 0.05) and chemiluminescence (P < 0.01). A significant correlation between blood PMN and mammary gland PMN was found only for the number of phagocytosing cells (r = 0.329; P < 0.01). Highly significant positive correlations (P < 0.01) were demonstrated between the number of phagocytosing PMN [a], phagocytotic index [b], and bactericidal activity [c] in both blood PMN (r(ab) = 0.602; r(ac) = 0.565; r(bc) = 0.529) and mammary gland PMN (r(ab) = 0.730, r(ac) = 0.618, r(bc) = 0.589). No significant correlation was demonstrated for non-stimulated (NS), zymosan-stimulated (ZS), or opsonized zymosan-stimulated (OZS) chemiluminescence with any of the other characteristics of phagocytotic activity, in either blood PMN or mammary gland PMN (P > 0.05). The animal was a highly significant source of variability for all the phagocytotic activity characteristics (P < 0.01). Udder quarter was a non-significant source of variability for all the characteristics of phagocytotic activity except for NS chemiluminescence (P < 0.05) and ZS or OZS chemiluminescence (P < 0.01). However, udder quarter was a non-significant source of variability of chemiluminescence indices ZS/NS and OZS/NS (P > 0.05). It has been demonstrated that in situ migration activity, the number of phagocytosing PMN, phagocytotic index, bactericidal activity of PMN and chemiluminescence indices of PMN collected from juvenile mammary glands of unbred heifers after influx induction can be regarded as candidate early markers of resistance to mammary infections.
Keywords: Blood; luminiscenční měření; Female; fagocytóza; krev; Animals; Breast; Cattle; ženské pohlaví; neutrofily; Luminescent Measurements; Phenotype; zvířata; Phagocytosis; fenotyp; Neutrophils; skot; prsy